1994
DOI: 10.7326/0003-4819-121-11-199412010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Folic Acid during Methotrexate Therapy for Rheumatoid Arthritis: A Double-Blind, Placebo-Controlled Trial

Abstract: Folic acid, an inexpensive vitamin, is safe in a broad range of doses and protects patients with rheumatoid arthritis who are taking methotrexate from toxicity while preserving the efficacy of methotrexate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
1
7

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 330 publications
(164 citation statements)
references
References 0 publications
4
147
1
7
Order By: Relevance
“…However, the effect of methotrexate treatment on lymphocyte proliferation and apoptosis in patients is transient (Յ48 hours) and is reversed by folic acid. In contrast, the antiinflammatory effects of methotrexate are lasting and are not reversed by either folic acid or folinic acid (17)(18)(19)(20)(21)(22). Previous research in animal models has demonstrated that low-dose methotrexate treatment promotes intracellular accumulation of AICAR, an intermediate in purine synthesis, and that accumulation of AICAR is associated with increased adenosine release into inflammatory exudates (1,23); adenosine mediates the antiinflammatory effects of methotrexate treatment in animal models of both acute inflammation and adjuvant arthritis (1,2,24).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of methotrexate treatment on lymphocyte proliferation and apoptosis in patients is transient (Յ48 hours) and is reversed by folic acid. In contrast, the antiinflammatory effects of methotrexate are lasting and are not reversed by either folic acid or folinic acid (17)(18)(19)(20)(21)(22). Previous research in animal models has demonstrated that low-dose methotrexate treatment promotes intracellular accumulation of AICAR, an intermediate in purine synthesis, and that accumulation of AICAR is associated with increased adenosine release into inflammatory exudates (1,23); adenosine mediates the antiinflammatory effects of methotrexate treatment in animal models of both acute inflammation and adjuvant arthritis (1,2,24).…”
Section: Discussionmentioning
confidence: 99%
“…A study in Psoriasis patients showed, that a dose of 20mg folic acid per week tended to decrease the efficacy of MTX (Chládek 2008). However, a study in rheumatoid arthritis showed that, administration of 5mg folic acid per week successfully reduced the hepatotoxicity without loss of efficacy (Morgan 1994). Thus, administration of 5 mg folic acid 24 hours after application of MTX is recommended (Pathirana 2009).…”
Section: Introductionmentioning
confidence: 99%
“…RA patients taking MTX are more likely to discontinue treatment because of adverse reactions than because of lack of efficacy (71). Stomatitis, nausea, diarrhea, and perhaps, alopecia caused by MTX may decrease with concomitant folic acid (81,82) or folinic acid (83) treatment without significant loss of efficacy. Relative contraindications for MTX therapy are preexisting liver disease, renal impairment, significant lung disease, or alcohol abuse.…”
Section: Pharmacologic Treatment Of Ramentioning
confidence: 99%